La Renta Mínima de Inserción: contradicciones e incertidumbres - Martín Giner, África (Cuadernos de Trabajo Social, 2007)
This article is the product of a social worker’s reflections on the contradictions and uncertainties of professional practice in the application of the «Law of Minimum Income for Social Integration» (Ley de Renta Mínima de Inserción) in the Community of Madrid (Law 15/2001, 27 December). The primary objective of this article is to point out some ideas to promote discussion and analysis of this benefit. The article begins with a contextualization of this benefit within the social-political environment. Then, it describes the contradictions and uncertainties that the law itself contains, as well as the ones that the law generates, the ones which social workers appropriate in the application of the law. Lastly, the author proposes some solutions to meet head on these contradictions and uncertainties.
Keywords: Contradictions contained in the Law; Autonomy vs dependence; Therapeutic tools; Support vs control; Ideological vs methodological attitude